Содержание психолого-педагогической работы с родителями и ближайшими родственниками поподготовке детей к кохлеарной имплантации - Арутюнян, И. А.
Basing on the work experience and carried out invest igation, in the article is found out the basic contents of psychopedagogical work with parents and relatives of the children who are to have helix vaccination, as well forecast ing issues of further results.
Keywords: Психология; Педагогика